A bioanalytical method development and validation for quantification of glycopyrrolate and neostigmine in rat plasma by LC-MS and its application to pharmacokinetic study - P. Vasu Babu; D. Akiladevi (Journal of Applied Pharmaceutical Research, 2025)
Background: After surgery, non-depolarizing neuromuscular blocking medications include neostigmine (NEO) and glycopyrrolate (GLY). Numerous traditional approaches, such as HPLC and UPLC procedures, are established for the quantification of GLY and NEO; nevertheless, they lack sensitive and specific analysis, especially in complex matrices.  Using the LC/MS approach, this work develops a bioanalytical method for quantifying both drugs in rat plasma and applies it to pharmacokinetic studies. Methodology: The plasma was extracted using acetonitrile, and Rivastigmine was employed as an internal standard. An MRM method with positive ions was used for multiple reactions. A  C18 column and a mobile phase - 70:30 mixture of acetonitrile and buffer was utilised at a flow rate of 1 ml/min. Plasma vortex for 10 minutes and centrifuged at 4000 rpm at 20°C. Validation and stability studies are conducted according to the ICH guidelines. The pharmacokinetic study by WinNonlin (Version 5.2) software.  Results and Discussion: Rt for Glycopyrrolate and Neostigmine at 1.838 and 2.800min. GLY has a precision (%CV) of 0.45 at HQC and 3.57 at LQC. NEO had a precision (%CV) of 1.13 at HQC and 2.79 at LQC. From 2 to 40 ng/mL of GLY and 10 to 200 ng/mL of NEO, the standard curves showed a linear relationship. LOD and LOQ for both drugs were 3pg/mL and 10pg/mL. Conclusion: A simple, affordable, reliable, and sensitive approach for quantifying GLY and NEO in rat plasma using LC-MS, with Rivastigmine serving as the internal standard, was developed, validated, and successfully applied in the pharmacokinetic study of rat plasma.